Direito, organizações e meios de comunicação: entre a rede de nomes de domínios (ICANN) e as redes sociais (Facebook) - Moura, Ariel Augusto Lira de (Universidade do Vale do Rio dos Sinos, 2023)
Legal normativity is not alien to the social changes brought about by introducing new forms of communication and the (re)organization of social practices. Digital communication and new technologies present themselves as the new social condition to be faced by legal theory. In this sense, it questions the observation of the changes of law in the face of the media and organizational assumptions of network culture. The central objective is to construct the analysis of law in the interplay between Law Theory, Organizational Theory, and Media Theory. Specifically, it aims to investigate the systemic-Luhmannian bases of the observation of legal communication and (re)construct the interconnection between Law, Organization, and Media Theories; analyze the theoretical changes operated by Gunther Teubner to observe the legal communication between regimes, organizations, and networks, as well as the thesis of the self-constitutionalization of the media, especially concerning the Internet, using the example of the governance of the ICANN (Internet Corporation for Assigned Names and Numbers); Finally, we analyze legal communication in the face of the phenomenon of platforms and digital communication, in partial synthesis with the theories developed. At this point, the case of (self-regulation of) content moderation and Meta's recent experiment of constituting an Oversight Board to judge cases about its own decisions and policies is central. The methodology is the pragmatic-systemic of Leonel Severo Rocha, together with bibliographic and documentary research techniques. The primary hypothesis is that the interrelation between the theories of Law, Organization, and Media applied to the observation of domain name networks and social networks are apt to verify the central dimensions of the transformations of legal communication in the digital realm.
Keywords: Teoria do Direito; Teoria das organizações; Teoria dos meios de comunicação; Plataformas; Comunicação digital; Law Theory; Organizational theory; Media theory; Platforms; Digital communication; ACCNPQ::Ciências Sociais Aplicadas::Direito